2014
DOI: 10.1055/s-0034-1373791
|View full text |Cite
|
Sign up to set email alerts
|

Bone and Soft Tissue Ablation

Abstract: Bone and soft tissue tumor ablation has reached widespread acceptance in the locoregional treatment of various benign and malignant musculoskeletal (MSK) lesions. Many principles of ablation learned elsewhere in the body are easily adapted to the MSK system, particularly the various technical aspects of probe/antenna design, tumoricidal effects, selection of image guidance, and methods to reduce complications. Despite the common use of thermal and chemical ablation procedures in bone and soft tissues, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 84 publications
(85 reference statements)
0
23
0
Order By: Relevance
“…A total of 1400–2600J energy delivered over 60–90 minutes has yielded 30–45% reductions in CIBP without complications. [84]…”
Section: 4 Therapeutic Management Of Cibpmentioning
confidence: 99%
“…A total of 1400–2600J energy delivered over 60–90 minutes has yielded 30–45% reductions in CIBP without complications. [84]…”
Section: 4 Therapeutic Management Of Cibpmentioning
confidence: 99%
“…Echo decorrelation imaging has been proposed as a method for monitoring of radiofrequency ablation (RFA), a currently important clinical treatment modality for unresectable liver cancer [3][4][5] and other tumors of soft tissue and bone. 6,7 Echo decorrelation imaging may also be applicable to monitoring of other thermal ablation methods, [8][9][10] including high-intensity focused ultrasound ablation. [11][12][13] Preliminary research has confirmed the ability of echo decorrelation imaging to predict heat-induced tissue coagulation for RFA and ultrasound ablation, both in vitro 1,14 and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the targeting error, the size of the tumor is another factor that clinicians should take into consideration prior to cryoablation. It has been advised that the probe must be placed approximately 1 cm from the tumor margins and 2 cm from each other . MRI‐guided cryoablation is recommended to treat larger lesions: its main advantage of precise visualization of the ablation zone ensures coverage of the total tumor while sparing neighboring healthy structures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been advised that the probe must be placed approximately 1 cm from the tumor margins and 2 cm from each other. 38,39 MRI-guided cryoablation is recommended to treat larger lesions: its main advantage of precise visualization of the ablation zone ensures coverage of the total tumor while sparing neighboring healthy structures. The proposed probe tracking method integrated with preprocedural MRI can be used to guide probe intervention.…”
Section: Discussionmentioning
confidence: 99%